Over-expression of human y-box binding proteini: a comparison between mammalian and bacterial expression system - Wong Jian, Yuan (Universiti Sains Malaysia, 2008)
The human Y -box protein I (YB- I) is a class of proteins involved in transcriptional and translational regulation of a wide range of genes. YB-1 is implicated in regulation of multiple cellular functions. Previous studies found that the YB-1 expression is upregulated in many tumours and is highly correlated with adverse cancer prognosis and resistance to cancer drugs. In order to further explore and understand the role of YB-1 in terms of transcriptional and translational regulation in development of malignancy tumours, an overexpression assay has been carried out. Two different recombinants YB- I plasmid, pGEX- 2TK-YB-1 and pREP-YB-1 were used to carry out over-expression assay in bacterial (Escherichia coli, BL-21) and mammalian system (He La cancer cells) respectively. The comparison was analyzed by western blot analysis using a YB-1 polyclonal antibody. The over-expression results show a different migration of YB-1 protein in bacterial and mammalian expression system compared to their actual theoretical size. Meanwhile, overexpression assay involved transfection of pREP-YB-1 into He La cells using calcium phosphate transfection method. Due to poor reproducibility and rare quantitative studies on the mechanisms of the calcium phosphate transfection, trouble shooting was done and the optimization steps were suggested in the discussion of this research.